AKUNTABILITAS KEPALA DESA DALAM PEMBANGUNAN JALAN DI DESA TAJA MULYA KECAMATAN BETUNG KABUPATEN BANYUASIN - Valentin, Puput; -, Isabella; -, Amaliatulwalidain (Universitas Mahendradatta Denpasar, 2024)
This study aims to find out how the village head is accountable for road construction in Taja Mulya Village, Betung District, Banyuasin Regency. In this study, researchers used qualitative methods because the data generated in this study were in the form of written and spoken words so that they were able to describe the situation in Taja Mulya Village. The qualitative method approach used by researchers in this study is a case study, data collection techniques consist of three methods, namely observation, interviews, documentation. And data analysis techniques by processing, reading all the data, starting coding all the data, applying the coding process, then showing how the descriptions and themes are expressed in the form of narrative and data analysis. This study uses the theory of accountability from Syahrudin Rasul, there are 5 (five) indicators, namely 1. Honesty and Law 2. Managerial 3. Program 4. Policy 5. Finance. the results of the research it was found that the accountability of the village head in road construction in Taja Mulya Village was not effective enough because there were still many damaged roads and also many roads that had not been cast or were still in dirt. The problems in the road construction process are constrained funds for the construction and repair of village roads so that road construction carried out in villages uses more funds from third parties such as the aspirations of the DPRD. The suggestion in this research is that the village government is more concerned with and pays more attention to the condition of village road construction and prioritizes the construction of damaged roads in order to facilitate access to schools and to the gardens where the community works. Keywords: Accountability, Development of village infrastructure, Village roads